Effects of an Antagonistic Analog of Growth Hormone-Releasing Hormone on Endometriosis in a Mouse Model and In Vitro. (November 2017) - Köster, Frank; Jin, Li; Shen, Yuanming; Schally, Andrew V.; Cai, Ren-Zhi; Block, Norman L.; Hornung, Daniela; Marschner, Gabriele; Rody, Achim; Engel, Jörg B.; Finas, Dominique
Endometriosis is a benign gynecologic disorder causing dysmenorrhea, pelvic pain, and subfertility. Receptors for the growth hormone-releasing hormone (GHRH) were found in endometriotic tissues. Antagonists of GHRH have been used to inhibit the growth of endometriotic endometrial stromal cells. In this study, the GHRH receptor splice variant (SV) 1 was detected in human endometrial tissue samples by Western blots and quantitative reverse transcription polymerase chain reaction (qRT-PCR). The highest messenger RNA (mRNA) and protein levels of SV1 were found in eutopic endometrium from patients with endometriosis compared to ectopic endometriotic tissues and endometrium from normal patients. The highest expression for GHRH mRNA was found by qRT-PCR in ectopic endometriosis lesions. In an in vivo mouse model with human endometrial explants from patients with endometriosis, 10 μg MIA-602 per day resulted in significantly smaller human endometrial xenotransplants after 4 weeks compared to mice treated with vehicle. The endometrial tissues expressed SV1 before and after xenotransplantation. The proliferation of endometrial stromal cells as well as the endometriosis cell lines 12-Z and 49-Z was decreased by exposure to 1 μM MIA-602 after 72 hours. The protein levels of epithelial growth factor receptors in 12-Z and 49-Z cell lines were reduced 48 and 72 hours after the administration of 1 μM MIA-602. MIA-602 decreased the activation of the MAP-kinases ERK-1/2. Our study demonstrates the presence of SV1 receptor as a target for treatment with GHRH antagonist in endometriosis. Endometrial tissues respond to MIA-602 with inhibition of proliferation in vitro and in vivo. The use of MIA-602 could be an effective supplement to the treatment strategies in endometriosis.